АСТАРЛЫ СӨЗДЕРДІҢ ДАМУ ЖОЛЫ. - Қатбаева, Г. Қ. (Journal of Oriental Studies, 2016)
В статье описывается история развития особенного вида фразеологизмов – иносказании в китайском языке. In given article the history of development of an especial kind of phraseological units – an allegory is described on Chinese language